CISD2 Attenuates Inflammation and Regulates Microglia Polarization in EOC Microglial Cells—As a Potential Therapeutic Target for Neurodegenerative Dementia - Lin, Muh-Shi (Frontiers in Aging Neuroscience, 2020)
Background. Accumulating evidence has demonstrated a significant association between microglia-driven inflammation in the brain and neurodegenerative dementia. We previously showed a significant decline in CISD2 expression in mice models with advanced age. Moreover, we observed that the knockdown of CISD2 led to remarkable inflammation and mitochondrial dysfunction in neural cells. In the present study, we investigated whether CISD2 attenuation influences anti-inflammatory effects and M1-M2 polarization in microglia. Materials and methods. The knockdown of CISD2 expression by siRNA (siCISD2) in EOC microglial cells was performed to mimic the age-driven decline of CISD2 expression. The extent of the inflammatory reaction, polarization in the M1/M2 spectrum, and NFκB activation were verified in EOC microglial cells exhibiting CISD2 deficiency. Results. In the cellular model of microglia, loss of CISD2 function mediated by siCISD2 exhibited a significant augmentation of proinflammatory signaling, as well as reduced expression levels of Arg-1, Ym1, IL-10, and BCL2. Attenuation of CISD2 expression led to a decrease in the proportion of the M2 phenotype of microglia (compared to M1). Enhanced DNA-binding activity of the NFκB p65 subunit was confirmed in cells transfected with siCISD2, as demonstrated by ELISA assay. Conclusions. To the best of our knowledge, this is the first report examining the following phenomena: (1) anti-inflammatory effects of CISD2 in microglia via NFκB regulation; (2) microglial CISD2 assistance in the restoration of M2 microglia phenotype. The anti-inflammatory effects of CISD2 in microglia eventually augment anti-apoptotic effects, which provides a rationale for the development of potential therapeutic target for neurodegenerative diseases and neurodegenerative dementia.